2021
DOI: 10.1177/23202068211052796
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Desensitizers, Temporary Cements, and Dentin Cleaning Methods on the Bond Strength of Self-Etch/ Adhesive Resin Cements to Dentin: An In Vitro Study

Abstract: Aim: The aim of this study was to evaluate the effect of desensitizer, temporary cements, dentin cleaning methods on shear bond strength (SBS) of self-etch and self-adhesive resin cements to dentin. Materials and Methods: Four hundred eighty buccal or lingual/palatine coronal portions of human molar teeth were mounted in the acrylic blocks. Teeth surfaces were prepared until the dentin was exposed. Specimens were divided into four groups. One group separated as control and three groups of teeth were treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…The results of this study revealed statistically non-significant differences in shear bond strength between both cleaning methods used ( P -value = 0.636). This finding supports the efficacy of the mechanical cleaning method and the chemo-mechanical method [ 25 ]. Both methods don’t only effectively remove the remnants of temporary cement, it also removes partially or totally the smear layer [ 14 ].…”
Section: Discussionsupporting
confidence: 84%
“…The results of this study revealed statistically non-significant differences in shear bond strength between both cleaning methods used ( P -value = 0.636). This finding supports the efficacy of the mechanical cleaning method and the chemo-mechanical method [ 25 ]. Both methods don’t only effectively remove the remnants of temporary cement, it also removes partially or totally the smear layer [ 14 ].…”
Section: Discussionsupporting
confidence: 84%